“I Hear No Men Talking About It”Male Stand-Up Comedians on Abortion - Kolehmainen, Tuula (AISNA (Associazione Italiana di Studi Nord-Americani), 2026)
In his 2023 stand-up special, From Bleak to Dark, comedian Marc Maron wonders why men
do not address the Supreme Court’s decision in Dobbs v. Jackson Women’s Health Organization,
which ended the constitutional right to abortion in the United States. The question of who
is, or should be, entitled to take a stand on the right to abortion, is up for debate, but so is
Maron’s claim that there are “no men talking about it.” Quite a few male comedians have
presented their – fictitious or real – views on reproductive justice on the stand-up stage, not
only in their post-Roe shows but also over the course of the past few decades. Stand-up comedy
is a unique forum for dealing with themes like gendered vulnerability and power relations,
even exposing views that would be considered offensive or even unlawful outside of the
comedic context. Narratives produced and reproduced in society are popularized in stand-
up comedy, and when they reach streaming services like Netflix, they reach huge audiences.
Seeing stand-up comedians as potential public intellectuals (Kunze and Champion), this
article explores how groups and communities are constructed and deployed in stand-up
(Brodie; Chesters), focusing on how US male comedians navigate the social debates on
the issue of abortion in their stand-up shows. While this article acknowledges that the
“definition of reproductive justice goes beyond the pro-choice/pro-life debate” (Ross and
Solinger 9), it will focus specifically on abortion for two reasons. First, extending the
discussion to parental rights and reproductive justice more generally would require a longer
discussion than is possible in the scope of this article, and second, focusing on abortion42 Tuula Kolehmainen
reflects more precisely what is found in the comedic material of male stand-up comedians
in the United States. Through analyzing a few examples from US comedians, I argue that
while stand-up comedy on the theme of abortion by men often reinforces patriarchal norms,
attitudes, and stereotypes, it also provides a platform for contesting them. I also argue that
this dual function operates through a rhetorical practice that positions men as outsiders.
While this rhetoric often deems women responsible for both pregnancies and abortions, as
“public intellectuals,” stand-up comedians have the potential to deconstruct narratives of
unequal gender relations and related social discussions.